Social Study on Capital Society in the Adaptation of the Kaba Volcano Eruption Disaster, Sumber Urip Village, Kec Selepurejang Lebong Regency, Bengkulu Province - Mandasari, Wiwik Riana; Hardi, Ode Sofyan (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
ABSTRACT : The purpose of this research is to propose the Study of Social Capital of the Community in the Adaptation of the Kaba Volcano Eruption Disaster, Sumber Urip Village, Kec. Selepu Rejang. Regency. Rejang Lebong. The type of research used is qualitative research, or the writing and behavior observed from the people (subjects) themselves. The sampling technique is purposive sampling. Data collection techniques used are interviews and documentation, then the data obtained are analyzed qualitatively to express the facts found in the field. The results of the research in the field are as follows: 1). Social Capital Studies Community is very related to the values, norms, social trust that collaborate in the environment, especially in the community tradition that produces local wisdom in the adaptation of the Kaba volcano eruption disaster. 2) The role of the government in disaster mitigation efforts in the form of periodic and measured training and simulations, coordination and cooperation in anticipation of facing disasters. 3) Preventive efforts in reducing disaster risk through local wisdom values ​​that are understood as social social capital. 4). Mitigation is generally interpreted as an action taken in minimizing the impact of disasters on both the loss of life, property that affects human life. Keywords : Social Capital, Adaptation, Volcano Eruption